Comparitive Analysis of Watermarking in Digital Images Using 3-Level DWT & LBP (International Journal of Engineering and Computer Science, 2018)
Digital watermarking has rise as a new research area for preventing illicit copying and duplication. In this paper two methods 3-level DWT & Local Binary Pattern (LBP) algorithm for watermarking in digital images are discussed. In order to compare the robustness of both algorithms noise attack is used.